The Narration of China (Part 2) : Medieval and Early Modern China, Expanding Horizons - Zhi, Che, (Ancient Languages and Civilizations ;, 2025)
Part Two of the Festschrift dedicated to William H. Nienhauser presents a collection of twelve academic papers that delve into the realms of poetry, fiction, and anecdotal writing from the Tang dynasty onwards. Readers will immerse themselves in the linguistic and literary intricacies of some of the most famous pieces of Tang era poetry, learn to see the city of Beijing through the eyes of a Portuguese explorer of the 16th century, dissect late pictorial depictions of Confucius in classroom settings, and discover how a real event might have inspired four separate Tang narratives to revolve around a female avenger.